(3TQM efXheI GdTjN GdSjO CMeO Hf YHO Gddg GdLRGFQis - (3CHhYHO Gddg GdSfhSis; (3CMeO Hf YHO Gddg GdLRGFQj,J (B899 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh YHO Gddg GdSfhSi ai TQM efXheI GdTjN GdSjO CMeO Hf YHO Gddg GdLRGFQi eG fUg hdaX GdTjN ai cJGH GdHjhY ef bhGYOg GdCUhdjI s
(3BNQgG (B:s
(3ajPhH GdYHO YfO ESJTYGQ gPG GdeYfi MjGA ef Gdehdi GdcQje Ld hYdG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B2511) s
Keywords: (3GdeLGejYs